Four new operations related to composition and their reformulated Zagreb index - K Pattabiraman; A Santhakumar (Indonesian Combinatorial Society (InaCombS), 2018)
The first reformulated Zagreb index EM1(G) of a simple graph G is defined as the sum of the terms (du + dv − 2)2 over all edges uv of G. In 2017, Sarala et al. introduced four new operations(F-product) of graphs. In this paper, we study the first reformulated Zagreb index for the F-product of some special well-known graphs such as subdivision and total graph.